Genetic engineering of Arabidopsis to overproduce disinapoyl esters, potential lignin modification molecules. Issue 1 (December 2017) - Lee, Shinyoung; Mo, Huaping; Kim, Jeong; Chapple, Clint
Abstract Background Monolignol-like molecules can be integrated into lignin along with conventional monolignol units, and it has been shown that the incorporation of non-canonical subunits can be used to generate hydrolysable lignin by introduction of ester linkages into the polymer and that this type of lignin is more easily removable. Disinapoyl esters (DSEs), which to some degree resemble the monolignol sinapyl alcohol, may be promising lignin modifying units for this purpose. As a first step toward determining whether this goal is achievable, we manipulated metabolic flux inArabidopsis to increase the amounts of DSEs by overexpressingsinapoylglucose:sinapoylglucose sinapoyltransferase (SST ) which produces two main DSEs, 1, 2-disinapoylglucose, and another compound we identify in this report as 3, 4-disinapoyl-fructopyranose. Results We succeeded in overproducing DSEs by introducing anSST -overexpression construct into thesinapoylglucose accumulator1 (sng1 -6 ) mutant (SST -OEsng1 -6 ) which lacks several of the enzymes that would otherwise compete for the SST substrate, sinapoyglucose. Introduction ofcinnamyl alcohol dehydrogenase -c (cad -c ) andcad -d mutations into theSST -OEsng1 -6 line further increased DSEs. Surprisingly, areduced epidermal fluorescence (ref ) phenotype was observed whenSST -OEsng1 -6 plants were evaluated under UV light, which appears to have been induced by the sequestration of DSEs into subvacuolar compartments. Although we successfully upregulated the accumulation of the target DSEs, we did not find any evidence showing the integration of DSEs into the cell wall. Conclusions Our results suggest that although phenylpropanoid metabolic engineering is possible, a deeper understanding of sequestration and transport mechanisms will be necessary for successful lignin engineering through this route.